ИСТОРИЧЕСКИЕ РЕКОНСТРУКЦИИ И АРХЕОЛОГИЧЕСКИЕ РЕАЛИИ (ямная культурно-историческая область) (Zaporizhzhia Historical Review, 2021)
The article is devoved of origin of the “Pit Grave culture”. The considerable differences in material culture of local versions and groups indicate that the basic for unity of it`s area is a common world outlook. The radiocarbon dates allow assuming its rather simultaneous and early formation in crisis` period of European history. The catastrofic collapse of the Chaleolithic cultures was connected with disintergration of Carpatho-Balkan metallurgical province. We might point to a five century-long chronological hiatus between thin province and the next, Circumpontic metallurgical province. In this period a new world outlook, was forming and it was called the Pit Grave Culture.